PERSEPSI PENGHUNI TERHADAP KENYAMANAN BERAKTIVITAS DI RUANG TERBUKA PERUMAHAN - Harefa, Anugerah Septiaman; Naibaho, Polin DR.; Rahmawati, Anna Lucy (Unika Santo Thomas, 2018)
A comfort open space has a function and a huge influence in housing because it becomes a means of activity throughout the housing dwellers. Debang Housing Taman Sari Medan is one of housing in Kecamatan Medan Selayang which has open space. The purpose of this research is to know the perception of occupant to the comfort of open space. There are several convenience factors that are used as indicators in research such as Circulation, Climate, Noise, Smell, Shape, Safety, Cleanliness, and Beauty. The research was done through qualitative descriptive analysis, where the data collection technique used questionnaire from the population and the specified sample. The process of collecting data, sampling technique until the criteria of research become an important process of research method. This study shows if the perception of occupants of the comfort of open space of housing Debang Taman Sari Medan is quite comfortable and needed supporting facilities for park users.